A component model for column face in bending of extended HolloBolt connections. (July 2021) - Mahmood, Mohammed; Tizani, Walid
Abstract: Extended HolloBolt (EHB) is a practical anchored blind bolting system for concrete-filled steel sections. One of the failure modes of EHB connections is the bending of the column face component. Up to date, no analytical model to estimate the strength and stiffness of this component have been proposed. This paper aims to develop such model to capture the principal aspects of the overall behaviour of the component, such as its strength and stiffness at different key stages, to represent the component behaviour. The component strength is assumed to be provided by the steel hollow section plate bending and the anchored action. The steel hollow section plate strength models were developed based on the yield line theory. The anchored strength was considered equivalent to the load required to initiate a concrete cone failure. The component stiffness models were formulated using elastic springs, one at each bolt location. The component stiffness was taken equal to the summation of springs stiffness as they act in parallel. The overall bending behaviour of the component was represented by a quad-linear model. The stiffness of the post yield parts of the model was considered as a percentage of the initial stiffness of the component. The model was validated with the available data in the literature and they provided reliable results, which can be considered as a benchmark for the design of EHB connections. This model can be later extended and generalized for other similar blind bolts connections. Graphical abstract: Unlabelled Image Highlights: Proposing a component model for the strength and stiffness of column face in Extended HolloBolts connections. The component strength is provided by the steel hollow section plate bending and the anchored action. The anchored strength was considered equivalent to the load required to initiate a concrete cone failure. The model can be extended and generalized for other similar blind bolt connections. The overall bending behaviour of the component can be represented by a quad-linear model.